2012
DOI: 10.1097/iae.0b013e318219e685
|View full text |Cite
|
Sign up to set email alerts
|

Critical Period for Foveal Fine Structure in Children With Regressed Retinopathy of Prematurity

Abstract: Preterm birth before 28 weeks of gestational age was associated with a failure of the inner retinal layers to migrate away from the fovea, resulting in increased foveal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 22 publications
10
50
1
3
Order By: Relevance
“…5 OCT has revealed changes not evident on ophthalmoscopy, but these can be compatible with good visual acuity. 6,7,[9][10][11] Authors have questioned the possibility of a non-retinal aetiology for visual deficits, so examination of the choroid is warranted. 1 The choroid serves functions including metabolic support for the RPE and retina, acting as a heat sink, and absorbing excess light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 OCT has revealed changes not evident on ophthalmoscopy, but these can be compatible with good visual acuity. 6,7,[9][10][11] Authors have questioned the possibility of a non-retinal aetiology for visual deficits, so examination of the choroid is warranted. 1 The choroid serves functions including metabolic support for the RPE and retina, acting as a heat sink, and absorbing excess light.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown shallowing of the foveal depression, thickening of the central macula, and a continuity of inner retinal layers across the fovea in those born severely preterm, often despite normal macular appearance on ophthalmoscopy. [6][7][8][9][10][11][12][13][14] However, these macular changes evident on OCT are still compatible with good visual acuity. 6,7,[9][10][11] This has prompted authors to suggest that other factors might be contributory to the variation in vision seen in these patients.…”
Section: Introductionmentioning
confidence: 97%
“…Because these factors have complicated relations with each other, it might be hard to find significant factor for the poor visual acuity in preterm patients. Although recent studies showed that retinal layer thickness at the fovea was not associated with visual acuity in preterm children, 8,24,25 Wang et al 1 reported that peripapillary RNFL thickness on the temporal side of the disc is related with visual acuity. Peripapillary RNFL is closely correlated with multiple visual deficits including visual field defect, low-contrast sensitivity, and abnormal electrophysiology results, as well as visual acuity in patients with various disease affecting the optic nerve.…”
Section: Variablementioning
confidence: 96%
“…Interestingly, although statistically significant differences in RNFL thicknesses between preterm and full-term children were observed in the average global RNFL thickness and in sectors including superior and nasal sides; the largest thinning of the mean RNFL thickness in preterm children was observed in the nasal sector, statistically significant correlations between baseline factors and RNFL thickness was mainly observed in RNFL thicknesses in the temporal sector. Wang et al 1,8 hypothesized that such abnormalities in the spatial profile of RNFL would be present based on abnormal inner retinal layers overlaying the fovea in preterm children. Recent studies have revealed that preterm children have thicker central maculae than children born at term, regardless of the presence of ROP.…”
Section: Variablementioning
confidence: 99%
See 1 more Smart Citation